Training on Making NPK Liquid Organic Fertilizer With The Application of Econobiotechnology - Abdul Razak; Eri Barlian; Herdi Herdi; Threo Wanda Marten; Muhamad Sholichin (Pascasarjana, Universitas Negeri Padang, 2022)
Policy reforms and research on agricultural ecology need to be intensified to reduce land degradation and the massive ecological and chemical impacts of soil chemical pollution. This is related to the increase in population that requires clothing, food, and welfare. Furthermore, although there has been a shift toward a form of agriculture with high-added value. This problem must be solved by diversifying efforts, applying ecology to agricultural cultivation land, and making breakthroughs in making organic fertilizers with various sources and environmentally friendly ways. This is rational and can be done by involving the industry, universities, and farmer groups who are smart and productive. Regarding farming diversification, The results obtained are by the solutions offered, farmers can make liquid organic fertilizers by utilizing water measuring 200 nm to 10 m of Micro-Nano-Bubbles (MNBs). This is following the concept and is the application of Econobiotechnology. Knowledge before participating in the training in making fertilizers Organic Liquid is 74%, while knowledge after attending training on making Liquid Organic Fertilizer is 91%. The interest in learning and making Liquid Organic Fertilizer is 40%.